PENGARUH PENERAPAN METODE MINDMAP DISERTAILKS TERHADAPPEMAHAMANKONSEP MATEMATIS SISWA KELAS VIII SMPN 1BATANG ANAI TAHUN PELAJARAN 2013/2014 - Yoma, Ranny Putri; Rahmi, Rahmi; Cesaria, Anna (Pendidikan Matematika, 2013)
The background of this research is due to the lack of mathematical concept understanding of VIII grade students in SMPN 1 BatangAnai.This problem is assumed to be caused by students which are less focused on teacherâs explanation and studentsâ noting which are still less attractive and effective. The purpose of this research is to know whether studentsâ understanding of mathematical concepts with the application of Mind Map learning methods and studentsâ worksheets is better than studentsâ understanding of mathematical concepts with convensional teaching for VIII grade students in SMPN 1 BatangAnai. The type of this research is experimental research with Randomized Control Group Only Design. Random technique is used to take the samples. The instrument used in this research is final test in the form of essay which contains the indicators of concept understanding. The test reability is 0,78. The data is analyzed by using one party t-test and with the help of Minitab. Based on the data analysis, it is obtained that the p-value = 0,000 smaller than Â = 0,05. In conclusion, the studentsâ understanding of mathematical concepts which applies Mind Map learning method and studentsâ worksheets is better than the conventional one.